Remittance Income in Nepal: Need for Economic Development - Gaudel, Yadav Sharma (Journal of Nepalese Business Studies, 2007)
ABSTRACT Remittance as a major source of foreign currency to the developing nation has become a substantial component of making current account surplus in the balance of payments. It is argued that many workers from Nepal going abroad for employment are no doubt young, energetic, laborious and enthusiastic. They do hard work for earning large remittance income to support their families. However, the downside of remittances reflects the view that remaining young generation for long time outside without family may increase their vulnerability and ultimately they will have a tendency to leave their homeland. Thus, in order to recover the loss of economically active labor force to the domestic economy, they should be encouraged to come back again with skilled knowledge for utilizing their savings and working experience for development to the productive areas in accordance with the priority of the national development plans. Journal of Nepalese Business StudiesIII/I pp. 9-17